Design of the 2d Platformer Game "Meru: Steps of Nature" - Avianto, Reza; Ciptaningrum , Rinawati (Syntax Literate, 2025)
Indonesia is located in the Pacific Ring of Fire, making it a country with 127 volcanoes, of which 80 are very active. The many mountains in Indonesia shape the culture of people who are active around mountains, one of which is mountain climbing activities. Mountain climbing is an adventure activity to the highest peak of a plain or mountain. At first, mountain climbing activities were only carried out by experienced people, now its popularity has made this activity a form of recreation and tourism. Mountain climbing activities raise issues about the environment, namely the existence of garbage left by irresponsible people can endanger the preservation of flora and fauna, thereby damaging the natural beauty of the mountains. Games like social media are designed to provide entertainment or challenges to players. Games have different types or genres, one of the genres that is quite popular is 2D platformer. This genre is a 2-dimensional-based game with gameplay related to moving and jumping between obstacles and objects referred to as platforms. The questions raised in this game are about gameplay, characters, and environment. The gameplay in this game includes: level 1; scoring system. Level 2; Time trial: The characters use 2D visuals (2 characters), and Envirometn takes advantage of the natural beauty of the mountains. Summary of the Meru game; The steps of Nature are as follows; 2-level gameplay, characters (main characters, and Non Playable Characters), and the natural landscape environment.